ナンキョク ジュウリョクハ ノ キセツ ヘンカ ト ハッセイゲン ニ カンスル ケンキュウ - 佐藤, 薫; サトウ, カオル; Sato, Kaoru (2010)
P(論文) ここ10年にわたり,気球や衛星観測,高解像モデルによる南極域重力波の研究が行われ,重力波の季節変化や大規模場への作用を議論する上で重要な,水平波長や位相速度に影響する発生源・発生メカニズムに関する理解が深まってきた.本論文では,このような背景の中,南極重力波の季節変化と発生源について,国立極地研究所プロジェクト「南極大気-雪氷-海洋圏における物質循環の総合解析」(2004-2009年度)に行われた2つの研究Yoshiki et al.(2004),およびSato and Yoshiki(2008)について紹介する.これらの研究は,それぞれ昭和基地の高層気象観測オリジナル高分解能データ,および,第43次日本南極地域観測隊にて行った高解像ラジオゾンデ集中観測に基づき行われた.前者では,成層圏最下層では重力波に特徴的な季節変化はなく,波のエネルギーは上部対流圏の非線形性の高い総観規模擾乱に伴い,低緯度の空気塊が侵入しているときに大きくなっている傾向がみられること,成層圏中部および下部では春に重力波エネルギーが極大となるが,季節内のより短い時間スケールでは,極夜ジェットが昭和基地に近づくときに強まることが示された.後者では,重力波の周波数・鉛直波数スペクトルを示し,極夜ジェットの非平衡度の高い領域から重力波が放射されている可能性を示した.これは,高解像気候モデルのシミュレーション結果とも調和的であった. In the last recent ten years, our knowledge of gravity waves in the Antarctic has been significantly improved through numerous studies using balloon and satellite observations and high-resolution model simulations. In this report, we introduce results from two studies which were performed as a part of the NIPR project "Integrated analysis of the material circulation in the Antarctic atmosphere-cryosphere-ocean" (2004-2009), i.e., Yoshiki et al. (2004) and Sato and Yoshiki (2008). These two studies focused on the seasonal variation and sources of the gravity waves in the Antarctic, because horizontal wavelengths and phase velocities depend largely on the wave sources. The former study used original high-resolution data from operational radiosonde observations at Syowa Station. In the lowermost stratosphere, gravity waves do not exhibit characteristic seasonal variation; instead, the wave energy is intensified when lower latitude air intrudes into the area near Syowa Station in the upper troposphere. This intrusion is associated with blocking events or developed synoptic-scale waves. In the lower and middle stratosphere, the gravity wave energy is maximized in spring and particularly intensified when the axis of the polar night jet approaches Syowa Station. The latter study is based on intensive radiosonde observation campaigns that were performed in 2002 at Syowa Station as an activity of JARE-43. Gravity ...